Framework for Distributed Evolutionary Algorithms in Computational Grids - Limmer, Steffen; Fey, Dietmar (Advances in Computation and Intelligence, 2010)
In the recent years an increasing number of computational grids have been built, providing an unprecedented amount of computational power. Based on their inherent parallelism, Evolutionary Algorithms are well suited for distributed execution in such grids. Unfortunately, there are several challenges concerning the usage of a grid infrastructure (e.g. the synchronization and submission of jobs and file transfer tasks). In this paper we present a new framework which makes a Globus based grid easily accessible for Evolutionary Algorithms and takes care of the parallelization. The usability is demonstrated by the example of an Evolutionary Algorithm for the Traveling Salesman Problem. © 2010 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD3.framew
Keywords: Computational Grid; Distributed Evolutionary Algorithm; Globus Toolkit; Traveling Salesman Problem